An Ottoman tragedy : history and historiography at play - Piterberg, Gabriel, 1955- (Studies on the history of society and culture ;, 2003)
In the space of six years early in the seventeenth century, the Ottoman Empire underwent such turmoil and trauma--the assassination of the young ruler Osman II, the re-enthronement and subsequent abdication of his mad uncle Mustafa I, for a start--that a scholar pronounced the period's three-day-long dramatic climax "an Ottoman Tragedy.